2006
DOI: 10.1128/jcm.00568-06
|View full text |Cite
|
Sign up to set email alerts
|

Synergistes Group Organisms of Human Origin

Abstract: The bacterial division Synergistes represents a poorly characterized phylotype of which only a few isolates have been cultured, primarily from natural environments. Recent detection of Synergistes-like sequence types in periodontal pockets and caries lesions of humans prompted us to search the R. M. Alden culture collection (Santa Monica, Calif.) for biochemically unidentifiable, slow-growing, obligately anaerobic gram-negative bacilli. Here we report on five clinical isolates cultured from peritoneal fluid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
3
50
0
1
Order By: Relevance
“…EF468684) and from Synergistes spp. isolated from human blood (EF551160, EF551161, EF551162) and peritoneal fluid samples (DQ412721, DQ412717, DQ412718) (Horz et al, 2006) (Fig. 2).…”
unclassified
See 1 more Smart Citation
“…EF468684) and from Synergistes spp. isolated from human blood (EF551160, EF551161, EF551162) and peritoneal fluid samples (DQ412721, DQ412717, DQ412718) (Horz et al, 2006) (Fig. 2).…”
unclassified
“…Using 16S rRNA gene targeted PCR assays, Godon et al (2005) explored 93 anaerobic environments and reported that members of the Synergistes group of organisms (SGOs) were present in 95 % of the ecosystems analysed and the sequences formed separate phylogenetic groups, although their proportion was generally below 1 %. Also, Horz et al (2006) have found that SGOs are ubiquitous in humans and have been detected in various infectious diseases. They identified clinically relevant isolates that make up three unique clusters that apparently occupy their own individual ecological niches within the human body such as peritoneal fluid, soft tissues and periodontal pockets, the latter having no isolated representatives.…”
mentioning
confidence: 99%
“…Strain RMA 10849 was obtained from the collection of the R. M. Alden Research Laboratory, Santa Monica, CA, USA. This isolate originated from a sacral wound and was previously described as an unnamed organism by Warren et al (2005) and further described as belonging to 'Synergistes' group organisms by Horz et al (2006). Colony morphology and the responses of the strains to special potency disks (Jousimies-Somer et al, 2002) were observed on Columbia sheep blood agar plates.…”
mentioning
confidence: 99%
“…To date, bacteria belonging to the phylum 'Synergistetes' have been found in a large range of ecosystems, including the guts of mammals (Godon et al, 2005). Culture-independent studies have demonstrated their presence in man during endodontic or periodontic infections, in dental caries (Munson et al, 2002(Munson et al, , 2004Siqueira & Rôças, 2005, 2007Hutter et al, 2003), in subgingival plaque (Paster et al, 2001), in faeces (Horz et al, 2006) and in vaginal flora (A. Damay, H. Marchandin, L. Roudière, C. Teyssier, H. Dechaud, H. Jean-Pierre, E. Jumas-Bilak, unpublished results). However, only eight human isolates have been reported to date (Munson et al, 2002;Warren et al, 2005;Horz et al, 2006).…”
mentioning
confidence: 99%
“…They are found in several microenvironments and constitute part of the human microbiota in health and disease [1][2][3][4], including the oral microbiota [5].…”
Section: Introductionmentioning
confidence: 99%